New occupational diseases legislation rules - Functioning evaluation - Marcin Rybacki; Ewa Wągrowska-Koski; Sylwia Świderska-Kiełbik; Jolanta Walusiak-Skorupa (Nofer Institute of Occupational Medicine, 2014)
Background: On 3 July 2009, new law pertaining to occupational diseases (ODs) became effective in Poland. The article presents opinions of the representatives of the 1st degree ODs certification entities and sanitary inspectorates on the changes in OD law and the problems that may cause difficulties and/or certification errors. Material and Methods: A questionnaire study was performed covering representatives of 20 voivodeship occupational medicine centers and 40 national district sanitary inspectorates. We received 57 completed questionnaires which were analyzed. Results: Positive opinions were expressed on changes in procedures on reporting suspected occupational diseases (50%), keeping time limits for diagnosing ODs (89.2%), and changes pertaining to entities responsible for certifying infectious ODs (92.9%). A large group of respondents (66.7%) was in favor of conducting jointly an occupational exposure risk analysis by occupational medicine physicians and occupational health and safety practitioners and/or sanitary inspectors. One-third of the respondents declared that changes in the list of ODs had no influence on the certification procedure. Conclusions: New law has improved the existing procedure of ODs certification. There is a need to elaborate detailed diagnostic guidelines on and criteria for ODs identification and recognition. A panel of experts should be established by the Ministry of Health to track the latest advancements in medicine and to update the list of ODs. Conducting jointly an occupational exposure risk analysis by occupational medicine physicians and occupational health and safety practitioners and/or sanitary inspectors should become a standard. Med Pr 2014;65(4):473-483